2011
DOI: 10.1074/jbc.m111.268821
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Transducin with Uncoordinated 119 Protein (UNC119)

Abstract: The key visual G protein, transducin undergoes bi-directional translocations between the outer segment (OS) and inner compartments of rod photoreceptors in a light-dependent manner thereby contributing to adaptation and neuroprotection of rods. A mammalian uncoordinated 119 protein (UNC119), also known as Retina Gene 4 protein (RG4), has been recently implicated in transducin transport to the OS in the dark through its interaction with the N-acylated GTP-bound transducin-␣ subunit (G␣ t1 ). Here, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Indeed, the rate of spontaneous activation (81) is very close to that of transducin return (56). Another study found that UNC119 is able to pull G␣ t from the membrane-bound transducin trimer, suggesting that no such spontaneous activation would be required (80). Once G␣ t is bound to UNC119, solubilization of G␤ 1 ␥ 1 could be subsequently facilitated by the isoprenoidbinding protein PrBP/␦ (82,83) or by another G␤ 1 ␥ 1 -interacting protein, phosducin, shown to reduce G␤ 1 ␥ 1 membrane affinity (84) and assist G␤ 1 ␥ 1 translocation, at least in the lightinduced direction (85).…”
Section: Mechanistic Insights Into Arrestin and Transducin Translocationmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, the rate of spontaneous activation (81) is very close to that of transducin return (56). Another study found that UNC119 is able to pull G␣ t from the membrane-bound transducin trimer, suggesting that no such spontaneous activation would be required (80). Once G␣ t is bound to UNC119, solubilization of G␤ 1 ␥ 1 could be subsequently facilitated by the isoprenoidbinding protein PrBP/␦ (82,83) or by another G␤ 1 ␥ 1 -interacting protein, phosducin, shown to reduce G␤ 1 ␥ 1 membrane affinity (84) and assist G␤ 1 ␥ 1 translocation, at least in the lightinduced direction (85).…”
Section: Mechanistic Insights Into Arrestin and Transducin Translocationmentioning
confidence: 96%
“…A motor-based mechanism (69,70) is unlikely to help as well because molecular motors are not known to extract lipidated proteins from membranes. A solution to this problem was offered (79) by demonstrating that the knock-out of UNC119, a protein capping the acylated N terminus of G␣ t (79,80), significantly impairs transducin return to the outer segment in the dark. In this mechanism, UNC119 acts by keeping G␣ t apart from G␤ 1 ␥ 1 and by maintaining G␣ t in the soluble form to allow its diffusion to the outer segment.…”
Section: Mechanistic Insights Into Arrestin and Transducin Translocationmentioning
confidence: 99%
“…The C-terminal domain of UNC119 shares significant sequence and structural homology with the prenyl-binding protein PrBP/δ [10, 11, 15]. Interestingly, unlike PrBP/δ, UNC119 selectively binds N-acylated (myristoylated) proteins, including N-acylated Gα t [11, 16, 17]. Furthermore, UNC119 is capable of interacting with heterotrimeric transducin (G t ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, UNC119 is capable of interacting with heterotrimeric transducin (G t ). UNC119 effectively displaced Gβ 1 γ 1 from G t and facilitated solubilization of Gα t and Gβ 1 γ 1 from membranes [16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation